Exploitation in college sports: no longer just a "man's game" - Agha, N.; Berri, D.; Brook, S. L.; Paulson, C. (Journal of Sports Economics, 2024)
Previous studies of college athlete compensation have generally focused on the "revenue sports" of football and men's basketball. Hence, wage exploitation is often considered a "man's game." In the 50 years since Title IX, many women's college sports have reported millions of dollars in revenue, suggesting wage exploitation is possible in college softball. Data on 19,760 athletes from 294 universities from 2012 to 2021, combined with two different sources of athletic revenue reach the same conclusion: wage exploitation exists in college softball. Furthermore, thousands of players generate more revenue in college than the wages they are likely to earn playing professional softball.